2011
DOI: 10.1590/s0001-37652011000400010
|View full text |Cite
|
Sign up to set email alerts
|

Modeling radiative transfer in tropical rainforest canopies: sensitivity of simulated albedo to canopy architectural and optical parameters

Abstract: This study evaluates the sensitivity of the surface albedo simulated by the Integrated Biosphere Simulator (IBIS) to a set of Amazonian tropical rainforest canopy architectural and optical parameters. The parameters tested in this study are the orientation and reflectance of the leaves of upper and lower canopies in the visible (VIS) and near-infrared (NIR) spectral bands. The results are evaluated against albedo measurements taken above the K34 site at the INPA (Instituto Nacional de Pesquisas da Amazônia) Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Quantitatively, investigating and understanding the relative contributions of different parameters to surface albedo is fundamental for its accurate modeling and retrievals in remote sensing (Gao et al, ) and also plays an important role in constraining the albedo uncertainties of the Earth's radiation budget in the climate modeling (Dickinson, ; Liang, ) and predicting how the ongoing changes in vegetation areas might affect the global climate (Lukeš et al, ). Some studies clearly demonstrated that the surface albedos of different plant species show different spatial and temporal patterns due to different canopy architecture and composition optical properties (Betts, ; Gao et al, ; Kuusinen et al, ; Kuusinen et al, ; Tian et al, ; Yanagi & Costa, ). For instance, there exists a general negative logarithmic relationship between LAI and the albedo on both the Mongolian Plateau and Tibetan Plateau (Tian et al, ); the foliage and branches clumping at the shoot and crown level can increase the probability for multiple interactions of photons in the canopy, thus reducing forest albedo (Hovi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitatively, investigating and understanding the relative contributions of different parameters to surface albedo is fundamental for its accurate modeling and retrievals in remote sensing (Gao et al, ) and also plays an important role in constraining the albedo uncertainties of the Earth's radiation budget in the climate modeling (Dickinson, ; Liang, ) and predicting how the ongoing changes in vegetation areas might affect the global climate (Lukeš et al, ). Some studies clearly demonstrated that the surface albedos of different plant species show different spatial and temporal patterns due to different canopy architecture and composition optical properties (Betts, ; Gao et al, ; Kuusinen et al, ; Kuusinen et al, ; Tian et al, ; Yanagi & Costa, ). For instance, there exists a general negative logarithmic relationship between LAI and the albedo on both the Mongolian Plateau and Tibetan Plateau (Tian et al, ); the foliage and branches clumping at the shoot and crown level can increase the probability for multiple interactions of photons in the canopy, thus reducing forest albedo (Hovi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Within each layer, the upward and downward radiation fluxes [3,9,21,28], respectively, are described by…”
Section: Upward and Downward Diffuse Radiative Fluxes: Two-streammentioning
confidence: 99%
“…Within each layer, the upward and downward radiation fluxes [1,4,7,9], respectively, are described by…”
Section: Upward and Downward Diffuse Radiative Fluxes: Two-streammentioning
confidence: 99%